Reflections on Teaching in Times of Crisis: Narrative Analysis of Urban Educators During the COVID-19 Pandemic - Sarah Brown; David Miller; Jessica Anderson (International Journal of Educational Narratives, 2025)
Background. The COVID-19 pandemic profoundly disrupted global education systems, forcing teachers to adapt to remote instruction, shifting expectations, and heightened emotional demands. Urban educators, in particular, faced layered challenges including technological inequity, socio-emotional strain, and intensified community needs. Purpose. This study explores how urban teachers experienced and responded to the crisis by analyzing their personal narratives of teaching during the pandemic. Method. Using a qualitative narrative analysis approach, the study collected data from 26 K–12 educators in three major metropolitan districts in the United States. Participants submitted reflective essays and engaged in semi-structured interviews between June and October 2021. Results. The findings reveal recurring themes of professional identity redefinition, emotional exhaustion, pedagogical innovation, and relational resilience. Teachers described a tension between systemic inadequacies and personal commitment, often framing their roles as both educators and emotional caregivers. Despite institutional constraints, many developed adaptive strategies that centered student well-being and equity. Conclusion. The study concludes that narrative inquiry provides essential insight into the lived complexities of teaching during crisis and underscores the need for systemic support structures that honor teachers’ emotional labor and professional agency.